Research Paper: Effectiveness of Resource Management Strategies and Achievement Goals Orientation in Predicting Academic Achievement Among Students With Hearing Impairment - Seyede Somayeh Jalil-Abkenar; Mohammad Ashori; Saeed Hasanzadeh (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective The purpose of the present research was to investigate the relationship of the resources management strategies and achievement goals orientation in predicting academic achievement in students with hearing impairment.  Materials & Methods The present research is a descriptive-analytical correlation study. The study population included students with hearing impairment who were aged 15-18 years. Eighty students (46 boys and 34 girls) were selected by convenient sampling method from Tehran province. The instruments of present research were resources management strategies questionnaire and achievement goals orientation questionnaire-revised. Data were analyzed by using mean, standard deviation, correlation coefficient, and stepwise regression along with SPSS (version 19). Results The normality of variables was tested. The Kolmogorov-Smirnov test showed that all variables were normal. The findings showed that resource management strategies (effort regulation and help-seeking) and achievement goals orientation (mastery approach goal and performance avoidance) have a positive and significant relationship with academic achievement (p<0.05). Mastery approach, effort regulation, help seeking and performance avoidance goal predicted 0.53 percent of the variance in academic achievement (p<0.05), and mastery approach goal had the most contribution to the prediction of academic achievement (p<0.001). Conclusion Variables such as resource management strategies and achievement goals orientation have a crucial role in predicting academic achievement in students with hearing impairment.